Toeholds, Bid Jumps, and Expected Payoffs in Takeovers - Betton, Sandra; Eckbo, B. Espen (Review of Financial Studies, 2000)
We estimate sequentially outcome probabilities and expected payoffs associated with first, second, and final bids in a large sample of tender offer contests. Rival bids arrive quickly and produce large bid jumps. Greater bidder toeholds (prebid ownership of target shares) reduce the probability of competition and target resistance and are associated with both lower bid premiums and lower prebid target stock price runups. The expected payoff to target shareholders is increasing in the bid premium and in the probability of competition, but decreasing in the bidder's toehold. The initial bidder's expected payoff is significantly positive in the “rival-bidder-win” outcome, in part reflecting gains from the pending toehold sale. Despite these dramatic toehold effects, only half of the initial bidders acquire toeholds.